Application of tyramide signal amplification‐fluorescence in situ hybridisation and flow cytometry to detection of Heterosigma akashiwo (Raphidophyceae) in natural waters - J Lee; T Katano; M Chang; M‐S Han (New Zealand Journal of Marine and Freshwater Research, 2012)
We developed protocols to analyse the cell cycle of Heterosigma akashiwo in the natural phytoplankton assemblage using tyramide signal amplification‐fluorescence in situ hybridisation (TSA‐FISH) and flow cytometry. We determined the optimum probe and formamide concentrations for the species‐specific TSA‐FISH probe to be 0.5 ng µL −1 and 40%, respectively. The probe did not hybridise to non‐target phytoplankton including Chattonella sp., which is closely related to Heterosigma and has high sequence similarity to it. We could successfully identify G1‐ and G2‐phase cells and the diel cell cycle of H. akashiwo not only in the laboratory but also in the field after TSA‐FISH. These results demonstrate that TSA‐FISH for H. akashiwo in natural coastal waters could serve as a powerful tool for understanding their bloom mechanism using flow cytometry.